DETERMINATION OF THE OPTIMAL NUMBER OF EMPLOYEES USING THE FULL TIME EQUIVALENT (FTE) METHOD AT PT. XYZ - muhammad dahlan; Nurhayati Rauf; Yusril Mahenra; Takdir Alisyahbana; Arfandi Ahmad; Andi Pawennari; Dirgahayu Lantara; Rahmaniah Malik (Center for Study and Journal Management FTI UMI, 2021)
Determining the optimal number of employees in a company is a basic condition that must be concern into account when drafting a work plan. The work design process ultimately aims for balance the physical and mental aspects of humans in completing certain tasks so that. Determination of the number of employees whit the existing workload will support employees performance in perform their duties optimally. The purpose of this research is to determine the optimal number of salesman based on the workload calculated using the Full Time Equivlent method. Based on the results of research at PT. Xyz used the method FTE is know that the workload of the 4 salesman is classified as overloaded. Where is sales I has a workload of 1.48, sales II has a workload of 1.70, sales III has a workload of 1.66, sales IV get a workload of 1.42. Based on the table of labor requirements to the FTE value, the number of initial salesman was 4 sales and the addition of the number of salesman is as many as 10 salesmen. So, the optimal number of salesmen in Makassar city is 14 salesmen.